BIOM-02. MUTATIONAL ANALYSIS AND SINGLE CELL SEQUENCING OF MELANOMA BRAIN METASTASES REVEALS BRAF STATUS CORRELATES WITH CLINICAL OUTCOME AND DIFFERENTIAL IMMUNE POPULATIONS. (14th November 2022) - Vasudevan, Harish; Delley, Cyrille; Aabedi, Alexander; Shukla, Poojan; Nguyen, Minh; Morshed, Ramin A; Young, Jacob S; Demaree, Ben; Diwanji, Devan; Hervey-Jumper, Shawn L; Boreta, Lauren; Fogh, Shannon; et al.
Abstract: Understanding the molecular landscape and microenvironment of melanoma brain metastases is critical to devise improved treatments. Here, we perform bulk and single cell genomic analysis of melanoma brain metastases to identify molecular correlates of clinical outcome. 84 consecutive patients who underwent surgical resection at a single institution with a histo-pathologically confirmed diagnosis of melanoma brain metastasis were retrospectively identified. In 60 patients (71%) with sufficient brain metastasis tissue for targeted next generation sequencing, DNA mutations were assessed with a CLIA certified sequencing assay. Single nuclear RNA sequencing using the 10x platform was performed on n=6 samples from treatment naïve patients. Overall survival (OS) and CNS progression free survival (CNS PFS) from time of brain metastasis diagnosis were estimated using the Kaplan-Meier method. The median patient age was 62 years old (range: 25-78 years), and the median clinical follow up was 17 months. A total of 33 patients (39%) had BRAF V600E melanoma brain metastases. Multivariate analysis incorporating age, performance status, and extracranial disease revealed BRAF status was an independent prognostic factor for OS (p< 0.05). In patients undergoing targeted next generation sequencing, the most common pathogenic variant was TERT promoter mutation (n=44; 73%). With regard to TCGA molecular melanoma subgroups, NRAS mutant (n=22; 37%) brain metastases were most common followed by BRAF mutant (n=20; 33%), NF1 mutant (n=11; 18%), and triple wildtype (n=7; 12%). Evaluation of clinical outcomes in the context of next generation sequencing results revealed no differences by TERT status but demonstrated worse overall survival in the BRAF mutant molecular group (p< 0.01, log-rank test). Single nuclear sequencing of 36, 115 nuclei across 6 samples revealed BRAF wildtype tumors exhibit greater infiltrating immune cell populations including microglia and T cell subtypes. Future work will require integration of these findings with different systemic therapy regimens and across larger, prospective, multi-institutional cohorts.